PEMANFAATAN PEMASARAN PRODUK IKAN TERI MELALUI E-COMMERCE SERTA PENGEMASAN SEDERHANA MENGGUNAKAN PRESS VACUUM - Pravitasari, Endyastuti; Permatasari, Sheila Silvia; Armenita, Kiko; Rahmadan, Yanuar (Jurnal Pemberdayaan Nusantara, 2023)
Kalibaru village is one of the salted fish centers in North Jakarta. However, the use of e-commerce for sales is rarely done. Not to mention, the packaging is less attractive to end consumers. The purpose of the community service activities in RW 9Kalibaru Village, Cilincing District, North Jakarta is to increase knowledge for MSMEs regarding the urgency of utilizing e-commerce to sell anchovy product and upgrade their packaging using press vacuum. The community service activities were organized using counseling and demo methodswhich divided into two sessions, related to product marketing through e-commerce and increasing product value withpress vacuum packaging. In this session, speakers were lecturers from Universitas 17 Agustus 1945 Jakarta who have their competence related with this topic. One of the findings obtained from this service activity is the difficulty of MSME, especially elder, to use e-commerce platform. Therefore, this counseling and demo are expected to help MSMEsfromRW 9 to be interested and more familiar with the e-commerce platform as a profitable place to selling their products.